Implementation of the Waiting List Policy in the Administration of the Hajj Pilgrimage at the Office of the Ministry of Religious Affairs of Central Maluku Regency - Mohamad Arsad Rahawarin; Hendry Selanno (PT. Banjarese Pacific Indonesia, 2026)
This study analyzes the implementation of the waiting list policy in the administration of the Hajj pilgrimage at the Office of the Ministry of Religious Affairs of Central Maluku Regency. A descriptive qualitative approach was used to examine how the policy is translated into public service practices, particularly in a local context where the waiting period has reached approximately 18 years, with about 2,500 prospective pilgrims and an annual quota of 135 people. Data were obtained through interviews, observation, and document review involving officials responsible for Hajj and Umrah services and relevant community informants. The data were analyzed using the interactive model of Miles, Huberman, and Saldana, consisting of data condensation, data display, and conclusion drawing. The findings show that policy implementation is supported by four interrelated factors: bureaucratic structure, resources, communication, and the disposition of implementing officers. A clear organizational structure and standard operating procedures facilitate coordination and accountability. Competent human resources, adequate facilities, and the use of Siskohat strengthen service accuracy and transparency. Multi-channel communication helps reduce misunderstanding, while professional and empathetic officer attitudes build public trust. The novelty of this study lies in its local-level analysis of Hajj waiting list implementation in an archipelagic regency. The study implies that transparent, responsive, and humanistic public services are essential for maintaining fairness and legitimacy in long-term Hajj queue management.